2016
DOI: 10.1002/jbm.b.33717
|View full text |Cite
|
Sign up to set email alerts
|

Insulin released from titanium discs with insulin coatings-Kinetics and biological activity

Abstract: Local administration of insulin from a titanium surface has been demonstrated to increase bone formation in non-diabetic rats. The authors hypothesized that insulin was released from the titanium surface and with preserved biological activity after the release. Thus, in the present in vitro study, human recombinant insulin was immobilized onto titanium discs, and the insulin release kinetics was evaluated using Electro-chemiluminescence immunoassay. Neutral Red uptake assay and mineralization assay were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Therefore, a reproducible thickness of <50 Å of insulin on the reference silica sample was used. However, to increase the amount of immobilized insulin, that is, the coating thickness, it might be advantageous to use a surface with different topography (micro‐pores) or hydrophilicity …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, a reproducible thickness of <50 Å of insulin on the reference silica sample was used. However, to increase the amount of immobilized insulin, that is, the coating thickness, it might be advantageous to use a surface with different topography (micro‐pores) or hydrophilicity …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that gene expression analyses of the peri‐implant bone would have shown different results, as compared to those obtained for the implant‐adherent cells. Furthermore, we have previously demonstrated that approximately 25% of initially immobilized insulin is released to the surroundings after 1 h of incubation of the implant in cell culture medium . The amount of insulin that remains on the surface in vivo after 3 weeks is presently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations